Best Practices in Academic Mentoring: A Model for Excellence - Jan M. Nick (Nursing Research and Practice, 2012)
Mentoring is important for the recruitment and retention of qualified nurse faculty, their ongoing career development, and leadership development. However, what are current best practices of mentoring? The purpose of this paper is to provide an overview of a model for excellence in establishing a formal mentoring program for academic nurse educators. Six themes for establishing a formal mentoring program are presented, highlighting best practices in mentoring as culled from experience and the literature. Themes reflect aims to achieve appropriately matched dyads, establish clear mentorship purpose and goals, solidify the dyad relationship, advocate for and guide the protégé, integrate the protégé into the academic culture, and mobilize institutional resources for mentoring support. Attending to the six themes will help mentors achieve important protégé outcomes, such as orientation to the educator role, integration into the academic community, development of teaching, scholarship, and service skills, as well as leadership development. The model is intended to be generalizable for faculty teaching in a variety of academic nursing institution types and sizes. Mentoring that integrates the six themes assists faculty members to better navigate the academic environment and more easily transition to new roles and responsibilities.